PENGARUH HIDROGENASI DALAM FASA LATEKS PADA KARET ALAM HEVEA BRASILIENSIS - E.Gumbira-Sa’id, Nelly Rahman dan Linda Febriyanti (Department of Agroindustrial Technology, Bogor Agricultural University, 2005)
AbstractNatural Rubber from Hevea brasiliensis is a polymer with a high content of unsaturated bonds in the molecule, which causes natural rubber to have a low resistance to oxidation, ozone and heat. However the weaknesses of natural rubber may be changed by modification of the molecule of the natural rubber. This study was done to modify natural rubber with hydrogenation using hidrazine hydrate, hydrogen peroxide and copper sulphate in latex phase. The results show that hydrogenated rubber has an increased strain, decreased molecule weight and decreased the Young modulus.Key words : Hevea brasiliensis, natural rubber, hydrogenation